Magnesium Sulfate Attenuates Lethality and Oxidative Damage Induced by Different Models of Hypoxia in Mice. (19th December 2020) - Mohammadi, Hamidreza; Shamshirian, Amir; Eslami, Shafagh; Shamshirian, Danial; Ebrahimzadeh, Mohammad Ali
Abstract : Mg 2+ is an important cation in our body. It is an essential cofactor for many enzymes. Despite many works, nothing is known about the protective effects of MgSO4 against hypoxia-induced lethality and oxidative damage in brain mitochondria. In this study, antihypoxic and antioxidative activities of MgSO4 were evaluated by three experimental models of induced hypoxia (asphyctic, haemic, and circulatory) in mice. Mitochondria protective effects of MgSO4 were evaluated in mouse brain after induction of different models of hypoxia. Antihypoxic activity was especially pronounced in asphyctic hypoxia, where MgSO4 at dose 600 mg/kg showed the same activity as phenytoin, which used as a positive control (P < 0.001 ). In the haemic model, MgSO4 at all used doses significantly prolonged latency of death. In circulatory hypoxia, MgSO4 (600 mg/kg) doubles the survival time. MgSO4 significantly decreased lipid peroxidation and protein carbonyl and improved mitochondrial function and glutathione content in brain mitochondria compared to the control groups. The results obtained in this study showed that MgSO4 administration has protective effects against lethality induced by different models of hypoxia and improves brain mitochondria oxidative damage.